Satuan Pendidikan Aman Bencana (SPAB) and Psychological First Aid (PFA) Workshop’ for Volunteers in Forum Pengurangan Risiko Bencana (FPRB) Kabupaten Bandung - Dwarawati, Dinda; Nugrahawati, Eni N.; Rozana, Anna; Husni Muizz, Ayu Tuty Utami Muhammad; Pudjiadi, Yasyfa Camilla; Azka, Hasybi Muhammad; Havila, Hasmi (KnE Social Sciences, 2023)
Strengthening the capacity of schools at the Kabupaten Bandung level in the government-initiated initiative of socializing Satuan Pendidikan Aman Bencana (SPAB) is one of the responsibilities of volunteers from the Forum Pengurangan Risiko Bencana (FPRB). However, there is currently a lack of qualified volunteers to serve as facilitators for disaster preparedness training for school personnel, including teachers and students. The objective of this workshop activity is to provide knowledge and skills to volunteers from the Bandung Regency Disaster Risk Reduction Forum (FPRB) to enhance their role as disaster volunteers. These FPRB volunteers operate under the guidance and supervision of the Bandung Regency Regent. They actively participate in various disaster-related activities such as disaster response, post-disaster rehabilitation and reconstruction, and disaster mitigation. The Bandung District consists of 31 sub-districts, most of which are prone to disasters. Workshop modules have been developed to facilitate the training of Forum Pengurangan Risiko Bencana (FPRB) volunteers. Subsequently, the FPRB volunteers, who will serve as facilitators, will conduct SPAB and PFA (Psychological First Aid) sessions. The training was completed within a two-day period. Keywords: volunteers, disaster education, school